Hero-Honda - Barua, S. K. (Samir K.); Balasubramanian, N. ([London] : SAGE, 2016)
The case focuses on governance issues that arise in case of joint ventures. The case is based on one of the most successful joint ventures in the history of corporate India between Honda Motor Company of Japan and the Munjal family of India. They established Hero Honda Motor Company in 1984. The company became the largest producer of motorcycles in the world.
Originally Published in: Barua, S. K., & Balasubramanian, N. (2015). Hero-Honda: Split Wide Open. BP0386. Ahmedabad: Indian Institute of Management, Ahmedabad.
Description based on online resource; title from home page (viewed on May 4, 2016).
Keywords: elektronické knihy; electronic books; Hero Honda Motor Company; Strategic alliances (Business) -- Case studies; Corporate governance -- Case studies; Strategic planning -- Case studies